2016
DOI: 10.3171/2015.4.jns142200
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma in the elderly: the effect of aggressive and modern therapies on survival

Abstract: abbreviatioNs EOR = extent of resection; GBM = glioblastoma; GTR = gross-total resection; HR = hazard ratio; KPS = Karnofsky Performance Scale; RT = radiotherapy; SRS = stereotactic radiosurgery; STR = subtotal resection; TMZ = temozolomide. obJective The prognosis of elderly patients with glioblastoma (GBM) is universally poor. Currently, few studies have examined postoperative outcomes and the effects of various modern therapies such as bevacizumab on survival in this patient population. In this study, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
63
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 52 publications
(66 reference statements)
9
63
4
1
Order By: Relevance
“…That finding contrasts with multiple earlier studies that demonstrated a strong predictive value for surgical resection in patients with gbm 15,20,21 . In our study, the number of non-elderly patients who did not undergo resection was quite small compared with the resected group (9 patients and 73 patients respectively).…”
Section: Figurecontrasting
confidence: 99%
“…That finding contrasts with multiple earlier studies that demonstrated a strong predictive value for surgical resection in patients with gbm 15,20,21 . In our study, the number of non-elderly patients who did not undergo resection was quite small compared with the resected group (9 patients and 73 patients respectively).…”
Section: Figurecontrasting
confidence: 99%
“…Lastly, in this elderly patient population only 21 % patients had MGMT promoter methylation and 42 % achieved a gross total resection. Consistent with the literature, both MGMT promoter methylation and gross total resection were associated with improved clinical outcomes in elderly GBM patients [26, 27]. …”
Section: Discussionsupporting
confidence: 86%
“…Our data showed the median age at diagnosis of IDH-mutant GBM and IDH-wildtype GBM was only 48 years and 50 years, respectively, which was similar with result (51 years) provided by Wang et al [15]. It's well-grounded that older age was a risk factor and always conferred to shorter survival [1820]. Therefore, we ascertained that older age was a major reason for the dismal prognosis of patients with GBM.…”
Section: Discussionsupporting
confidence: 87%